Validity and inherent viscosity of the quiet direct simulation method - Jermy M.C.; Lim C.-W.; Cave H.M. (2023)
The Quiet Direct Simulation (QDS) scheme is a numerical method for modelling gas flows, based on kinetic theory, with some similarities to the Lattice Boltzmann Method (LBM). It differs from LBM notably in that the discrete molecular velocities are not constant but are reset each timestep according to local values of bulk velocity and temperature. For this reason it performs well in highly compressible flows. Two features of the scheme limit its accuracy in low Mach number flows. QDS assumes a Maxwell distribution of molecular velocities. The validity of this assumption may be tested by calculating the gradient Knudsen number and average number of collisions per timestep. The separation of collision and streaming leads to excessive diffusion of momentum, leading to a very high effective viscosity of the modelled gas when the grid spacing is larger than the mean free path. This numerical dissipation is different in character from the dissipation due to the finite order of the spatial reconstruction, common to all finite volume methods, which is also present. The effective viscosity is quantified for simple shear flows and tested in models of a 2D channel flow. A crude model of intermolecular collision during streaming is implemented and shown to reduce the effective viscosity. 2011 American Institute of Physics.